Ehrlichia chaffeensis replication sites in adult Drosophila melanogaster - Drolia, Rishi (Kansas State University, 2012)
Ehrlichia chaffeensis is a Gram-negative, obligatorily intracytoplasmic bacterium and the causative agent of a tick-borne disease, human monocytic ehrlichiosis. In vertebrates, E. chaffeensis exhibits tropism for monocytes /macrophages. However, no clear requirements for cell tropism have been defined in ticks. Previously, our group identified two host genes that control E. chaffeensis replication in vivo in Drosophila. We used these two genes, CG6364 and separation anxiety (san) to test the hypothesis that E. chaffeensis replicates in arthropod hemocytes. Using the UAS/GAL4 RNAi system, we generated F1 flies (RNAi flies) and confirmed ubiquitous-or tissue-specific reduction in the transcript levels of the targeted genes. When RNAi flies were screened for Ehrlichia infections, we found that when either CG6364 or san were specifically suppressed in the hemocytes or in the fat body E. chaffeensis failed to replicate or cause infection. Deletion of these genes in the eyes, wings or the salivary glands did not impact fly susceptibility or bacterial replication within these organs. Our data demonstrate that in Drosophila, E. chaffeensis replicates within the hemocytes, the insect homolog of mammalian macrophages, and in the fat body, the liver homolog of mammals. This study provides insights about replication sites of E. chaffeensis in arthropods.
Keywords: Ehrlichia chaffeensis; Drosophila melanogaster; Biology (0306)